QPSK communication between two nodes using USRP - Ng, Eric Jia Qiang (2017)
In Nanyang Technological University (NTU), the Satellite Research Centre (SaRC) had six different satellite mission since the year of 2011. SaRC had successfully launched six satellite to space, which is named VELOX-I, VELOX-II, and VELOX-PIII. As these three satellites are classified under nano or pico satellite class. In this final year project, the main objective is to be able to set up communication between the satellite ground stations using the USRP X312 device, USRP E312 device, and ZC706 device and integrate it together with the Software Defined Radio under the platform of GNU Radio software. The first task for this FYP is to be able to synchronize the USRP X310 with the Windows PC. By assigning the fixed IP address to the device itself, the Windows PC will be able to detect the USRP X310. Hence, it is able to allow the USRP X310 to transmit and receive the signal of the desired outcome. Not only that, it can also display the necessary signal spectrum that it had received from other devices. The second task for this FYP is to be able to enable communication between USRP E312 and the Windows PC. Hence, a simple Radio Frequency (RF) channel can be set up through this communication channel. By having this communication, USRP E312 is able to receive signal spectrum from the RF. Not only that, by implementing GNU Radio system in the communication between USRP E312 and Windows PC, USRP E312 will allow the user to receive a signal from a specific and tuneable frequency band. The third and final task for this FYP is to be able to set up a communication between Xilinx ZC706, the Windows PC, and the external monitor. Hence, a simple set up is required to display out the transmitting and receiving of the signal spectrum. Not only that, by changing the setting and the wiring connection, it is able to change the display from the external monitor to the main Windows PC. Next, by connecting an Ethernet crossover cable, it is able to set up a communication connection between two ZC706 boards. Lastly, by setting to the correct transmitting and receiving frequency, it will allow two different boards of ZC706 to communicate.